Medición de la huella hídrica de la Universidad Politécnica Salesiana campus Sur. - Ortiz Sarango, Cristian Alfonso (2018)
In the present work the Water Footprint has been determined, from now on will also be called WF. The WF is the result of the main activities carried out at the Universidad Politécnica Salesian, Sede Quito, Campus Sur, which directly or indirectly use water resources. The Total Water Footprint, has been calculated separately in several of its components. First Direct Water Footprint and then Indirect Water Footprint. Data relevant to water consumption was collected for the calculation of Direct Water Footprint and the consumption of certain products for the calculation of Indirect Water Footprint. The methodology according to Water Footprint Network was used to calculate the Direct Water Footprint which in turn is the result of the total sum of these three: WF Blue, WF Green and WF Gray. The electric power and paper consumption data were used in the determination of Indirect Water Footprint, for each of these parameters it was necessary to apply conversion factors, which represent the water consumption derived from these activities. Finally, with the sum of the water footprints, the Total Water Footprint was determined, which is an indicator of sustainability regarding the use of water and can be used as a tool for decisions that intend to carry out activities that are friendly to the environment.